The incidence of brain lesions in central precocious puberty: The main cause for Chinese boys was idiopathic. (30th May 2021) - Wang, Jinling; Zhan, Shumin; Yuan, Jinna; Ullah, Rahim; Dong, Guanping; Wu, Wei; Huang, Ke; Fu, Junfen
Abstract: Objective: Many studies show that brain lesions are the main cause of central precocious puberty (CPP) in males. However, the association rate has not been reported in China. This study aimed to assess the frequency of both abnormal and likely pathologic brain lesions by magnetic resonance imaging (MRI) in Chinese boys with CPP. Design: This is a retrospective cross‐sectional single‐centre study. Patients: 396 CPP boys were recruited from 2011 to 2019 in Children's Hospital, Zhejiang University School of Medicine, and 129 were eligible for our study. Measurements: Diagnosis age, bone age, weight (kg), height (cm), puberty stage, MRI results and levels of sexual hormone were analysed. Results: The number of CPP boys is increasing from 2011 to 2019 in China. Brain MRI findings were normal in 83.7% of CPP boys. Only 21 (16.3%) CPP boys were found with abnormal MRI findings including hamartoma, pineal cyst and other minor changes. Conclusion: In China, there is an increasing trend of male CPP over the last decade and the main cause is idiopathic, rather than pathogenic brain lesions. Further investigations about the aetiology for CPP with pathological brain lesions are needed.